Comparative Analysis: Adobe Illustrator vs. Canva for Graphic Design Projects - Lalu Amarin Emgirinata; M Raga Al Abtad Purma; M. Hasan Amir Husen (Secure And Knowledge-Intelligent Research in Cybersecurity And Multimedia (SAKIRA), 2024)
This article discusses the comparison between two popular multimedia software tools, Adobe Illustrator and Canva, in terms of functionality, ease of use, and utility across various graphic design projects. Adobe Illustrator is renowned as a professional vector design tool with advanced features, while Canva offers a more user-friendly approach with a wide range of templates and ready-to-use design elements. Through this comparative analysis, the article aims to provide insights into the strengths and weaknesses of each software to help users select the tool best suited to their needs. In this digital era, graphic design has become increasingly important for various purposes—personal, business, and professional. Graphic design helps effectively convey information and capture the audience's attention. Two popular multimedia software tools for graphic design are Adobe Illustrator and Canva. Each has its advantages and drawbacks, and choosing the right software depends on the user's needs and skill level.